Risks for Vascular Injury During Anterior Cervical Spine Surgery: Prevalence of a Medial Loop of Vertebral Artery and Internal Carotid Artery. Issue 4 (February 2016) - Wakao, Norimitsu; Takeuchi, Mikinobu; Nishimura, Manabu; Riew, K. Daniel; Kamiya, Mitsuhiro; Hirasawa, Atsuhiko; Imagama, Shiro; Kawanami, Katsuhisa; Murotani, Kenta; Takayasu, Masakazu
Abstract : Study Design: Observational study using a retrospective single-institute database. Objective: To investigate the prevalence of a medial loop (ML) of the vertebral artery (VA) and internal carotid artery (ICA), which might be an anatomical risk factor for arterial injury in anterior cervical surgeries. Summary of Background Data: Anterior cervical spine surgeries are generally considered to be safe and effective. VA injury is one of the most serious complications during anterior procedures. Several articles have reported this complication, which might be because of the anomalous course of VA at V2 segment. The prevalence and anatomical features of those high-risk cases were, however, not investigated. Methods: Consecutive Japanese subjects, who underwent contrast-enhanced computed tomography (CT) or computed tomographic angiography (CTA) for reasons other than evaluation of cervical artery disease from November 2011 to October 2012 in our institution, were reviewed. Exclusion criteria included poor images, past surgery, and endovascular intervention of cervical spine and its vessels. The definition of ML was set as the course of VA and ICA extended medially inside the uncovertebral joint. We also investigated whether those anomalous courses were detectable by plain CT. Results: A total of 1251 subjects with age ranging from 14 to 93 years with a mean of 56.1 years were surveyed. Among them, 1054 subjects were eligible and the others were excluded. A total of 421 subjects were male, and 633 were female. There were 10 cases (1%) with an ML of the VA, and 2 (0.2%) cases with a medial loop of internal carotid artery. Five of the 10 cases with a medial loop of vertebral artery were aberrant into the vertebral body, which were detectable by plain CT. Importantly, the other five cases could not be seen on the CT. Conclusion: One percent of all subjects showed higher anatomical risk for VA and ICA injury during anterior surgery, half of which were undetectable by plain CT. Preoperative evaluation for vascular anatomy may be necessary for safer surgical treatment. Level of Evidence: 4